2015
DOI: 10.1016/j.ajhg.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Mutations in the Basic Domain of TWIST2 Cause Ablepharon Macrostomia and Barber-Say Syndromes

Abstract: Ablepharon macrostomia syndrome (AMS) and Barber-Say syndrome (BSS) are rare congenital ectodermal dysplasias characterized by similar clinical features. To establish the genetic basis of AMS and BSS, we performed extensive clinical phenotyping, whole exome and candidate gene sequencing, and functional validations. We identified a recurrent de novo mutation in TWIST2 in seven independent AMS-affected families, as well as another recurrent de novo mutation affecting the same amino acid in ten independent BSS-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 67 publications
3
66
0
1
Order By: Relevance
“…Gorlin et al [1990] suggested BSS and AMS to be allelic entities due to the substantial phenotypic overlap. This was confirmed by an international collaborative study as it demonstrated that both disorders can be caused by heterozygous mutations in TWIST2 [Marchegiani et al, 2015]. TWIST2 is located at 2q37.3, encodes for a bHLH protein that binds to E-box DNA motifs as a heterodimer with other similar proteins, and is considered to act as a negative regulator of transcription.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Gorlin et al [1990] suggested BSS and AMS to be allelic entities due to the substantial phenotypic overlap. This was confirmed by an international collaborative study as it demonstrated that both disorders can be caused by heterozygous mutations in TWIST2 [Marchegiani et al, 2015]. TWIST2 is located at 2q37.3, encodes for a bHLH protein that binds to E-box DNA motifs as a heterodimer with other similar proteins, and is considered to act as a negative regulator of transcription.…”
Section: Introductionsupporting
confidence: 52%
“…The term ablepharon is therefore in fact a misnomer, but for historical reasons we suggest to keep the term AMS unchanged. The anterior parts of the eyelids vary in their underdevelopment from being extremely small in AMS to minor reduction in size in BSS, to even less marked expression in a coloboma in a mosaic patient and absence of eyelashes only of the medially lower lid [Marchegiani et al, 2015]. The underdeveloped anterior lamella causes ectropion, causing in turn lagophtalmus, which may need surgical correction [McCarthy and West, 1977;David et al, 1991;Price et al, 1991;Cruz et al, 1995;Ferraz et al, 2000;Stevens and Sargent, 2002;Brancati et al, 2004;Martins et al, 2010;Roche et al, 2010;Rohena et al, 2011;Feinstein et al, 2015;Marchegiani et al, 2015].…”
Section: Facementioning
confidence: 98%
See 2 more Smart Citations
“…The authors of 13 publications responded. Three BSS individuals [Barber et al, 1982;Dinulos and Pagon, 1999;Tenea and Jacyk, 2006] and 1 AMS individual [Stevens and Sargent, 2002] were lost to followup, so we gathered questionnaires from 10 BSS individuals and 2 AMS individuals [David et al, 1991;Mazzanti et al, 1998;Stevens and Sargent, 2002;Brancati et al, 2004;Haensel et al, 2009;Martins et al, 2010;Roche et al, 2010;Marchegiani et al, 2015;Singh et al, 2016]. The questionnaire was written in English, and in case a participant was unable to read and write English, local persons acted as interpreters.…”
Section: Methodsmentioning
confidence: 99%